Elimination of the Sugar Transporter GAT1 Increased Xylanase I Production in Trichoderma reesei - Xu, Wenqiang; Fang, Yu; Ding, Mingyang; Ren, Yajing; Meng, Xiangfeng; Chen, Guanjun; Zhang, Weixin; Liu, Weifeng (Frontiers in Microbiology, 2022)
The filamentous fungus Trichoderma reesei secretes large quantities of cellulases and hemicellulases that have found wide applications in industry. Compared with extensive studies on the mechanism controlling cellulase gene expression, less is known about the regulatory mechanism behind xylanase gene expression. Herein, several putative sugar transporter encoding genes that showed significant upregulation on xylan were identified in T. reesei. Deletion of one such gene, gat1, resulted in increased xylanase production but hardly affected cellulase induction. Further analyses demonstrated that deletion of gat1 markedly increased XYNІ production at the transcriptional level and only exerted a minor effect on XYNⅡ synthesis. In contrast, overexpressing gat1 caused a continuous decrease in xyn1 expression. Deletion of gat1 also affected the expression of xyn1 and pectinase genes when T. reesei was cultivated with galacturonic acid as the sole carbon source. Transcriptome analyses of Δgat1 and its parental strain identified 255 differentially expressed genes that are enriched in categories of glycoside hydrolases, lipid metabolism, transporters, and transcriptional factors. The results thus implicate a repressive role of the sugar transporter GAT1 in xyn1 expression and reveal that distinct regulatory mechanisms may exist in controlling the expression of different xylanase genes in T. reesei.